Pulsatile operation of a continuous-flow right ventricular assist device (RVAD) to improve vascular pulsatility - Ng, Boon Chiang; Kleinheyer, Matthias; Smith, Peter Alex; Timms, Daniel Lee; Cohn, William E.; Lim, Einly (Public Library of Science, 2018)
Despite the widespread acceptance of rotary blood pump (RBP) in clinical use over the past decades, the diminished flow pulsatility generated by a fixed speed RBP has been regarded as a potential factor that may lead to adverse events such as vasculature stiffening and hemorrhagic strokes. In this study, we investigate the feasibility of generating physiological pulse pressure in the pulmonary circulation by modulating the speed of a right ventricular assist device (RVAD) in a mock circulation loop. A rectangular pulse profile with predetermined pulse width has been implemented as the pump speed pattern with two different phase shifts (0% and 50%) with respect to the ventricular contraction. In addition, the performance of the speed modulation strategy has been assessed under different cardiovascular states, including variation in ventricular contractility and pulmonary arterial compliance. Our results indicated that the proposed pulse profile with optimised parameters (Apulse = 10000 rpm and ωmin = 3000 rpm) was able to generate pulmonary arterial pulse pressure within the physiological range (9–15 mmHg) while avoiding undesirable pump backflow under both co- and counter-pulsation modes. As compared to co-pulsation, stroke work was reduced by over 44% under counter-pulsation, suggesting that mechanical workload of the right ventricle can be efficiently mitigated through counter-pulsing the pump speed. Furthermore, our results showed that improved ventricular contractility could potentially lead to higher risk of ventricular suction and pump backflow, while stiffening of the pulmonary artery resulted in increased pulse pressure. In conclusion, the proposed speed modulation strategy produces pulsatile hemodynamics, which is more physiologic than continuous blood flow. The findings also provide valuable insight into the interaction between RVAD speed modulation and the pulmonary circulation under various cardiovascular states.